Descriptive and normative ethical behavior appear to be functionally distinct. Issue 1 (28th September 2020) - Cox, David J.
Abstract : Many philosophers and scientists have described a scientific approach to ethical behavior. Historically, ethical behavior has been categorized as descriptive (i.e., what is right) or normative (i.e., why it is right). Whether this topographical distinction is functionally relevant is unknown. In 2 experiments, participants chose what behavior was correct and why. In Experiment 1, participants did not agree on either of these measures. Normative ethical behaviors were also well described by common Western theories of bioethics (i.e., consequentialism, deontology, and virtue theory). In Experiment 2, manipulating the ethical context led to within‐subject changes in responses to what, why, or both. Importantly, change in what rarely coincided with change in why, suggesting descriptive and normative ethical behaviors are functionally distinct. A visual‐descriptive model describing a functional approach to descriptive and normative ethical behavior is provided. Behavior analysts interested in observing, measuring, and changing ethical decision‐making should consider collecting data on descriptive and normative ethical behaviors.